Pengaruh Tumpangsari Jagung (Zea mays L.) dengan Famili Fabaceae terhadap Populasi dan Pertumbuhan Gulma Serta Efisiensi Penggunaan Lahan DI Lahan Kering - Ngawit, I Ketut; Farida , Nihla; Haryanto, Hery (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
The research aims to examine the effect of intercropping corn with the fabaceae family on weed population and growth as well as land use efficiency. The research was designed with a single factor treatment with a randomized block design in 3 blocks. This treatment is a monocrop planting pattern and intercropping of corn with peanuts, soybeans, green beans, red beans and cowpeas. The parameters observed include the weight of dry biomass and dry seeds of plants, the population and weight of dry biomass of weeds. As a result of the research, 16 weed species were found with high species diversity, evenness, dominance and abundance. It was found that 6 species of weeds were dominant and existed during plant growth, namely Cyperus rotundus, Paspalum vasginatum, Leersia hexandra, Digitaria longiflora, Cynodon dactylon, Synedrella nodiflora and Amaranthus gracilis. Peanuts and cowpeas are suitable for intercropping with corn because they can reduce the population and growth of weeds and do not compete with corn. Soybeans, green beans and red beans are not suitable for intercropping with corn because they are not effective in suppressing the population and growth of weeds and compete with corn, so that corn yield losses due to weed competition are 62.37% - 63.77% and corn yield losses due to crop competition reach 38.20 % – 40.96 %. The best ecological and agronomic land use efficiency was obtained from intercropping corn with peanuts and cowpeas, with land equalization values ​​(LEV) based on plant biomass weight of 1.90 and 1.89 and based on dry seed weight of 1.79 and 1.78 (LEV > 1).